Peran Guru Sekolah Dasar Dalam Implementasi P5 Di SD Al-Fatah 1 Ambon: Indonesia - Samsudin, Siti H.; Salamor, Lisye; Gaite, Titus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the role of teachers in the implementation of the Pancasila Student Profile Strengthening Project (P5) at SD Al-Fatah 1 Ambon as an integral part of the Merdeka Curriculum. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation. The results of the study indicate that teachers serve as facilitators, motivators, and mentors in shaping students' character in line with Pancasila values such as creativity, critical thinking, collaboration, and independence. Although teachers have made significant efforts through project-based learning, creative use of simple materials, and group work, challenges still arise in the form of limited facilities, time constraints, and lack of environmental support. Therefore, innovation in learning and collaboration among schools, families, and communities are essential to ensure a more optimal implementation of the P5 program.